The association between unilateral and bilateral performance-related measures in elite female soccer players: a multifaceted investigation - Paravlic, Armin Huso; Abazovic, Ensar; Milanović, Zoran; Vučković, Goran; Spudić, Darjan; Hadzic, Vedran; Pajek, Maja; Vodičar, Janez (Frontiers in physiology, 2024)
PURPOSE: The present study aimed to investigate a) the associations between bilateral performance utilizing countermovement jump (CMJ), squat jump (SJ), speed and unilateral CMJ, isokinetic peak torque in knee extension and flexion with angular velocities of 60°/s and 180°/s and tensiomyography (TMG) parameters; b) whether the asymmetries derived from unilateral tests are associated with bilateral CMJ, SJ and speed in elite female soccer players. METHODS: Thirty-five elite female soccer players (average age: 20 ± 5 years) completed CMJ, SJ, speed, isokinetic muscle strength and TMG tests. RESULTS: Compared to the non-dominant leg, the dominant leg demonstrated greater peak torque output in both knee flexion (7.4%) and knee extension (5.6%) isokinetic tasks, as well as m. vastus medialis contraction time (7.6%), and soccer-specific agility test (4.1%). Conversely, the hamstring to quadriceps peak torque ratio at 180°/s (8.5%) was significantly greater in the non-dominant leg. The associations between CMJ, SJ and speed performance were positive and ranged from weak (r = 0.350) to high (r = 0.710). For speed and TMG-derived variables, correlations were negative and ranged from weak (r = -0.345, p = 0.042, for vastus medialis contraction time) to moderate (r = -0.530, p = 0.001, for biceps femoris contraction time). Furthermore, both bilateral CMJ and SJ negatively correlated with TMG-derived variables, ranging from weak (r = -0.350, p = 0.039, for vastus lateralis contraction time) to moderate (r = -0.537, p = 0.003, for rectus femoris contraction time). CONCLUSION: The overall significant, albeit inconsistent, correlations between the diverse performance scores obtained highlight the necessity for a multifaceted and thorough diagnostic strategy in female soccer players.
Keywords: neuromuscular function; muscle contractile properties; physical function; running speed and agility; TMG; women’s football; power; strength